The politics of the anti-realist trend in contemporary Philippine fiction - Fajutagana, Leonora M. (UP Los Baños Journal, 2009)
Among the most conspicuous trends in literary practice is the increasing bias for non-realist narrative modes in fiction which reflects, among others, the postmodern skepticism towards positivist discourses. This paper considers this a major shift and explores some of its implications on the novel as genre and on literature in general.